Children’s Language Learning Vocabulary Through Mobile Applications: Duolingo - Sri Devi, Gusti Ayu Komang Friska (Stilistika : Journal of Indonesian Language and Literature, 2022)
This research article aims to investigate how the influence of Duolingo can help improve children’s vocabulary. The data were obtained from the 10 children of 7th graders as the sample that was collected in 1 main place that was the researcher’s house to make it easier to collect and observe the data. This study used the theory of language learning proposed by Halliday (1978). This study used a pre-experimental research design with a pre-test and post-test. The 10 children as the sample were practicing using Duolingo apps for 10 days, during which they had to answer 1 lesson consisting of 10 to 15 exercises every day. The collected data in this study were quantitatively analyzed by observing the children that consisted of some procedures. This study used two research instruments, namely, tests and questionnaires to answer the research questions. How can Duolingo help children improve their vocabulary? Furthermore, to present the data, this study used the tables and charts which were elaborated with symbols and numbers, to ensure validity and reliability, and described the ethical consideration in terms of the involvement of the respondents. The result of this study showed that by using Duolingo as a learning medium, children can master most of the vocabulary from all the given exercises. The scores they obtained for the post-test were much higher than the scores for the pre-test.